2020
DOI: 10.1017/s0950268820000382
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hepatitis A in Greece in the last decade: management of reported cases and outbreaks and lessons learned

Abstract: Hepatitis A is a mandatory notifiable disease in Greece. Here, we present the epidemiological data for 2009–2018 and the results of outbreak investigations performed, and discuss future public health priorities. Overall, 1193 cases were reported; 320 migrants/refugees, 240 Roma, 112 travellers and 521 from the general population. The median age of the affected general population (37 years) had an increasing trend (from 30.8 years in 2009 to 40.5 in 2018, P < 0.001) and was significantly higher than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Germany (n=9) (16, 29, 32, 34, 37, 52, 56, 59, 62), Spain (n=8) (43-45, 48, 61, 63-65), Italy (n=6) (33, 36, 40, 46, 47, 58, 60) and Greece (n=5) (28, 42, 50, 51, 54, 55) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
“…Germany (n=9) (16, 29, 32, 34, 37, 52, 56, 59, 62), Spain (n=8) (43-45, 48, 61, 63-65), Italy (n=6) (33, 36, 40, 46, 47, 58, 60) and Greece (n=5) (28, 42, 50, 51, 54, 55) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
“…Roma people are recognized as a high-risk group for HAV infection, in addition to migrants, travelers to endemic countries, and men who have sex with other men[ 19 , 20 ]. In Slovakia and Greece, the countries with a significant number of Roma residents, several hepatitis A outbreaks were reported over the last 15 years[ 16 , 19 , 21 ]. In the period between 2009 and 2018, 1193 cases of HAV infection were reported in Greece.…”
Section: Hepatitis Amentioning
confidence: 99%
“…In the period between 2009 and 2018, 1193 cases of HAV infection were reported in Greece. Roma people accounted for approximately 20% of all infections, with 80.7% of cases affecting Roma children under 15 years old, whereas in the non-Roma population, the percentage of children was significantly lower (5.3%)[ 19 ]. Even though the HAV vaccine is mandatory for all children in Greece since 2008, the study from 2013 showed that only 22.6% of Roma children were vaccinated against HAV[ 22 ].…”
Section: Hepatitis Amentioning
confidence: 99%
See 2 more Smart Citations